The roles and applications of extracellular vesicles in cancer - Clotilde Théry; Daniel Louvard (Molecular Oncology)
Extracellular vesicles (EVs) have been studied for several decades and are attracting growing interest among life scientists and oncologists. Understanding the extent of diversity of their cellular origins, structure, molecular composition, and consequently functions is still under progress. EVs offer numerous diagnostic and therapeutic possibilities, but many fundamental questions about their functions need to be resolved in order to effectively and safely implement their applications in the treatment of human diseases.